1993
DOI: 10.2169/internalmedicine.32.547
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Acute Hepatitis B Virus Infection while Receiving Immunosuppressants after Renal Transplantation.

Abstract: A 47-year-old man with acute hepatitis B virus (HBV) infection who had been receiving immunosuppressants after renal transplantation developed progressive liver failure. During the clinical course (approximately 7 months), anti-HBc IgM antibody and HBV-DNApolymerase levels remained high, but the serum alanine aminotransferase (ALT) level was consistently less than 150 K.U. Histopathologic examination of the liver showedsubmassive hepatic necrosis without significant inflammation accompanied by marked fibrosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Rapid progression of hepatitis B disease has been reported after liver transplantation 2 and fatal acute hepatitis B virus infection has been reported in patients receiving immunosuppressants after renal transplant. 3 While facing the higher probability of becoming chronic carrier state in immunocompromised/immunosuppressed hosts, patients with rapid progression to FHF should be evaluated for liver transplantation judiciously. Temporary liver support should be also prepared if the donor is not available.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid progression of hepatitis B disease has been reported after liver transplantation 2 and fatal acute hepatitis B virus infection has been reported in patients receiving immunosuppressants after renal transplant. 3 While facing the higher probability of becoming chronic carrier state in immunocompromised/immunosuppressed hosts, patients with rapid progression to FHF should be evaluated for liver transplantation judiciously. Temporary liver support should be also prepared if the donor is not available.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Rao et al [9] observed that hepatitis B infection was associated with poor prognosis in renal transplant recipients. Moreover, Hamada et al [10] and Chen et al [11] reported the cases of fatal acute hepatitis and fibrosing cholestasis hepatitis in HBsAg carriers after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported an absence of an immune response in biopsies of RT patients with acute liver failure. 113,114 Two other studies reported that mononuclear cell infiltrates were predominant. 115,116…”
Section: Nmldmentioning
confidence: 99%